PERBANDINGAN EFEKTIVITAS TERAPI MUSIK KLASIK DENGAN AROMATERAPI MAWAR TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI - Damanik, Siti Rahmalia Hairani; Hidayah, Nurul '; Elita, Veny ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Hypertension is high blood pressure defined as repeatedly elevated blood pressure exceeding 140 over 90 mmHg. Non-pharmacological therapies that can be applied to hypertension is classical music therapy and rose aromatherapy. The aim of this research was to compare the effectiveness of classical music therapy and rose aromatherapy on blood pressure in patients with hypertension in Puskesmas Lima Puluh Pekanbaru. This research used quasy experimental design with pre test and post test design with two comparison treatments. The total number of samples in this study were 30 respondents, who were divided into 15 as classical music therapy group and 15 as rose aromatherapy group. The sampling technique used purposive sampling techniques, with inclusion criteria. The blood pressure was measured with omron digital sphygmomanometer and observation sheet. The data used an average measurement of systolic and diastolic blood pressure for 3 days pre-test and post-test. The analysis used univariate and bivariate by using dependent t test and independent t test. The results of this research showed that there was no significant difference between the two therapies are provided, with p systole=0.642 and p diastole=0.596 > α (0.05). The reducing mean in systolic and diastolic blood pressure was 17.36 mmHg and 6.85 mmHg in the classical music therapy group and 13.76 mmHg and 3.76 mmHg in the rose aromatherapy group. Based on these results, the researcher suggested for health care provider to apply one of the both therapy as complementary therapies for patients with hypertension.